Systematic ajmaline challenge in patients with long QT 3 syndrome caused by the most common mutation: a multicentre study - Hohmann, Stephan; Rudic, Boris; Tueluemen, Erol; Borggrefe, Martin (Europace, 2017)
Aims: Overlap syndromes of long QT 3 syndrome (LQT3) and the Brugada syndrome (BrS) have been reported. Identification of patients with an overlapping phenotype is crucial before initiation of Class I antiarrhythmic drugs for LQT3. Aim of the present study was to elucidate the yield of ajmaline challenge in unmasking the Brugada phenotype in patients with LQT3 caused by the most common mutation, SCN5A-E1784K. Methods and results: Consecutive families in tertiary referral centres diagnosed with LQT3 caused by SCN5A-E1784K were included in the study. Besides routine clinical work-up, ajmaline challenge was performed after informed consent. A total of 23 subjects (11 female, mean age 27 ± 14 years) from 4 unrelated families with a family history of sudden cardiac death and familial diagnosis of the SCN5A-E1784K mutation underwent ajmaline challenge and genetic testing. Sixteen subjects (9 female) were found to be heterozygous carriers of SCN5A-E1784K. Ajmaline challenge was positive in 12 out of the 16 (75%) mutation carriers, but negative in all non-carriers. Following ajmaline, a significant shortening of the rate-corrected JT (JTc) interval was observed in mutation carriers. The baseline JTc interval was significantly longer in mutation carriers with a positive ajmaline challenge compared with those with a negative one. Conclusion: Overlap of LQT3 and BrS in patients carrying the most common mutation is high. Therefore, ajmaline challenge represents an important step to rule out potential BrS overlap in these patients before starting sodium channel blockers for the beneficial effect of QT shortening in LQT3.
Gesehen am 24.08.2018
Online publish-ahead-of-print 2 December 2016